The Influence of the Use of Augmented Reality Technology in Learning Arabic in increasing students' learning motivation - sidik, jafar; Akhiryani, Atna; Supiyandi, Supiyandi; Suyitno, Suyitno; Sarip, Mohammad (International Journal of Language and Ubiquitous Learning, 2024)
Background. Along with the development of the times and changes in the way of looking at the use of technology in learning Arabic is becoming more sophisticated and complicated. For that, the use of Augmented Reality technology is applied in learning Arabic in order to improve the learning process. Augmented Reality technology is a technology that in its use can combine digital elements that can be seen virtually and can also be presented in the form of 3D animation. Purpose. The aim of this research is to determine the effect of using Augmented Reality technology in Arabic language learning on student learning motivation. Apart from that, to create innovative and creative Arabic language learning for students. Method. The research method used in this research is a quantitative method with a randomized control experimental approach. Data was collected through questionnaires in the form of questionnaires. Results. The results of this research show that the use of Augmented Reality technology in Arabic language learning can increase student learning motivation. Students who are involved in Augmented Reality-based learning show a higher level of motivation, as well as a more active level of participation in the learning process. The use of Augmented Reality technology strengthens student engagement with learning material, increasing their understanding of the Arabic language context. Students are also increasingly interested in learning Arabic. Conclusion. The conclusion of this research states that Augmented Reality technology in Arabic language learning has a positive impact on student learning motivation. This emphasizes the importance of implementing technological innovation in education to increase learning effectiveness and strengthen student engagement. This research provides a basis for further development in the use of Augmented Reality technology in the context of learning Arabic and other subjects.